PENGARUH PENAMBAHAN KONSENTRASI MINYAK PADA PROSES FATLIQUORING TERHADAP PENINGKATAN KELEMASAN KULIT ARTIKEL GOAT BATTING PEARL WHITE EMBOSS - Zulfa Ashari; Elis Nurbalia; Hermawan Prasetyo (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2021)
The purpose this final project to explain the increase in skin elasticity of goat batting pearl white emboss with the addition of the concentration of oil used in the fatliquoring process. This research was carried out from February to March 2021. The material used in this study was 25 pieces of wet blue goat skin with an area of ​​140 sqft and a weight of 20 Kg. The auxiliary materials used in the fatliquoring process are Pellan 802, Lipoderm Liquor SAF, and Peramit MLN. The results of the initial formulation showed that the skin with slackness was still not up to standard, so the reformulation was added to the percentage of concentration used was 4% Pellan 802, 2% Lipoderm Liquor SAF, and 0.25% Peramit MLN to increase skin slackness in goat batting pearl white embossed. Based on the results of the physical test for the softness test before reformulation the results were 4.4 mm and for the skin after reformulation the results were 5.8 mm. In addition, the tensile strength, elongation and tear strength of goat batting pearl white embossed skin also increased, indicating that the reformulation in the fatliquoring process succeeded in increasing the slackness of goat batting pearl white embossed skin.